Clinical and molecular diagnosis of pathologic complete response in rectal cancer: an update. (3rd October 2018) - Timmerman, Corey; Taveras, Luis R.; Huerta, Sergio
ABSTRACT: Introduction : The standard of care for locally advanced rectal cancer includes neoadjuvant chemoradiation with subsequent total mesorectal excision. This approach has shown various degrees of response to neoadjuvant chemoradiation (ranging from complete response to further tumor growth), which have substantial prognostic and therapeutic implications. A total regression of the tumor is a predictor of superior oncologic outcomes compared with partial responders and non-responders. Further, this concept has opened the possibility of nonoperative strategies for complete responders and explains the widespread research interest in finding clinical, radiographic, pathologic, and biochemical parameters that allow for identification of these patients. Areas covered : The present review evaluates the most recent efforts in the literature to identify predictors of patients likely to achieve a complete response following neoadjuvant treatment for the management of rectal cancer. This includes clinical predictors of pathologic complete response such as tumor location, size, and stage, molecular predictors such as tumor biology and microRNA, serum biomarkers such as carcinoembryogenic antigen and nomograms. Expert commentary : There has been significant progress in our ability to predict pathological complete response. However, more high-quality research is still needed to use this concept to confidently dictate clinical management.